2004
DOI: 10.1167/iovs.03-0827
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Retinal Detachment–Associated Photoreceptor Cell Loss in Bax-Deficient Mice

Abstract: Apoptosis is a major mechanism leading to photoreceptor cell death after RD. Blockage of the activity of the proapoptotic molecule Bax in a knockout mouse model prevents photoreceptor cell apoptosis and cell loss. These data suggest that the Bax-mediated apoptotic signaling pathway plays a critical role in RD-associated photoreceptor cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 32 publications
7
73
2
4
Order By: Relevance
“…The results also revealed that exogenous EPO significantly upregulated the expression of Bcl-X L and reduced the expression of caspase-3, indicating that the combination of EPO and EPOR may induce Bcl-2 antiapoptotic gene expression by signal transduction pathways, and inhibits apoptosis by suppressing the mitochondrial release of cytochrome C and regulating intracellular Ca 2 þ levels. Histopathological findings revealed that the ONL thickness in all groups was only slightly reduced at 14 d after RD; although this reduction was significant, it was less than that reported in previous studies, such as those of Berglin et al 33 and Yang et al, 34 who reported that the ONL thickness was reduced by half at 14 days after local RD in rabbits. This variation may be due to inter-species differences, the concentrations of sodium hyaluronate used, or the retinal uplift height.…”
Section: Eyecontrasting
confidence: 60%
“…The results also revealed that exogenous EPO significantly upregulated the expression of Bcl-X L and reduced the expression of caspase-3, indicating that the combination of EPO and EPOR may induce Bcl-2 antiapoptotic gene expression by signal transduction pathways, and inhibits apoptosis by suppressing the mitochondrial release of cytochrome C and regulating intracellular Ca 2 þ levels. Histopathological findings revealed that the ONL thickness in all groups was only slightly reduced at 14 d after RD; although this reduction was significant, it was less than that reported in previous studies, such as those of Berglin et al 33 and Yang et al, 34 who reported that the ONL thickness was reduced by half at 14 days after local RD in rabbits. This variation may be due to inter-species differences, the concentrations of sodium hyaluronate used, or the retinal uplift height.…”
Section: Eyecontrasting
confidence: 60%
“…Earlier studies mainly focused on the mitochondrion-mediated pathway; the existence of mitochondrion-mediated pathway has been confirmed in the apoptosis of photoreceptors whereby the inhibition of key factors in above pathway prevented the photoreceptors from apoptosis. [8][9][10] However, the inhibitors can only partly rescue photoreceptors, suggesting the existence of other pathways for the apoptosis process after RD.…”
Section: Introductionmentioning
confidence: 99%
“…7 Other events affecting the photoreceptors include apoptosis and loss of structural integrity, both of which are thought to contribute to the vision impairment following RD. [8][9][10] Misalignment of photoreceptors, measured by Stiles-Crawford function, may also be a problem after RD repair. 11,12 Mü ller cells have been shown to react within 15 min of RD, 13 with proliferation and hypertrophy of their processes seen as little as two days postdetachment.…”
Section: Introductionmentioning
confidence: 99%
“…10,24,25 Accumulation of glutamate has been observed in animal models of retinal ischaemia, [26][27][28][29] and animal studies of RD have shown excess glutamate levels and lower glutamine synthetase (GS) activity within the retina. [30][31][32] Moreover, increased levels of glutamate were recently found in the vitreous fluid of human subjects with RD.…”
Section: Introductionmentioning
confidence: 99%